Integrated analysis of the genetic basis of suicidal behavior: what has been shown by structural genetic studies so far. (April 2018) - Bozorgmehr, Ali; Ghadirivasfi, Mohammad; Tavakoli, Mostafa; Rahmani, Hamid; Heydari, Fahimeh; Shahsavand Ananloo, Esmaeil
Abstract : Objective: In recent decades, the role of genetic factors in the predisposition to suicidal behavior has attracted considerable attention. Although each genetic investigation appears to be valuable, no one study on its own can comprehensively explain the etiology of suicidal behavior. Methods: In this study, using a broad literature review, we found the suicide-associated gene coexpression network. In addition, cytoband, molecular function, biological process, cellular component, tissue-based expression, and disease/disorder enrichment analyses were carried out to determine the most central cellular and molecular infrastructures involved in suicidal behavior. Results: The reconstructed network consisted of 104 genes, including 91 previously known genes and 13 novel genes, and 354 interactions. Topological analysis showed that in total, CCK, INPP1, DDC, and NPY genes are the most fundamental hubs in the network. We found that suicide genes are significantly concentrated within chromosomes 11 and 6. Further analysis showed that monoaminergic signal transduction, especially through GPCRs, in the cingulate gyrus, superior prefrontal gyrus, dorsal striatum, and the cerebellum are the main, deficient routes in suicide. Moreover, it turned out that genetically, suicidal behavior is more likely in patients with mood and affective disorders. Conclusion: Like other behavioral disorders, suicide has a complex and multifactorial basis and at present, the only approaches to the integrated study of such disorders are computer-based methods. The results of such studies, although subject to a degree of uncertainty, however, can pave the way for future basic and clinical studies. Abstract : Supplemental Digital Content is available in the text.